Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1002/bem.20676
|View full text |Cite
|
Sign up to set email alerts
|

Human cognitive performance in a 3 mT power-line frequency magnetic field

Abstract: Extremely low frequency (ELF, <300 Hz) magnetic fields (MF) have been reported to modulate cognitive performance in humans. However, little research exists with MF exposures comparable to the highest levels experienced in occupations like power line workers and industrial welders. This research aims to evaluate the impact of a 60 Hz, 3 mT MF on human cognitive performance. Ninety-nine participants completed the double-blind protocol, performing a selection of psychometric tests under two consecutive MF exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…Some references [1]; [25]; [29]; [36]; [42]; [62]; [87]; [94]; [101]; [102] discussed the problems of the irreproducible bioeffects of weak magnetic fields. Some references [1]; [36]; [62]; [101]; [102] explained the reasons in different view points.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some references [1]; [25]; [29]; [36]; [42]; [62]; [87]; [94]; [101]; [102] discussed the problems of the irreproducible bioeffects of weak magnetic fields. Some references [1]; [36]; [62]; [101]; [102] explained the reasons in different view points.…”
Section: Discussionmentioning
confidence: 99%
“…An increased risk of amyotrophic lateral sclerosis (ALS) in workers occupationally exposed to ELF-MFs were observed in Huss, et al [21]. Kleijn, et al [22]; Zhang, et al [23]; Schüz, et al [24]; Tang, et al [25]; Fixler, et al [26]; Wang, et al [27]; Prato, et al [28]; Corbacio, et al [29]; Vanderstraeten and Gillis [30]; Bowman, et al [31]; Prato, et al [32]; Burda, et al [33]; Burger, et al [34] reported the other biological effects of ELF-MFs (0 to 300 Hz) fields. Smith, et al [58]; Lednev [59]; Blanchard and Blackman [60]; Binhi [61] proposed the mechanisms of biological effects of ELF-MFs which are cyclotron resonance theory and it's new interpretation,the ion parametric resonance model and an interference of ions bound within proteins.…”
Section: The Hyperfine Coupling Mechanism Of Biological Effects On Elmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the most part of the studies, ELF-MFs are safe and well tolerated (Di Lazzaro et al, 2013). However, previous papers have showed deterioration in memory and learning processes after ELF-MFs exposure both in animals (Jadidi et al, 2007) and in humans (Podd et al, 2002;Corbacio et al, 2011). Instead, other studies have reported, after chronic ELF-MFs exposure, a positive effect in social recognition memory (Varró et al, 2009) and spatial learning (Liu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These studies have highlighted the role of neuronal morphology and orientation were critical in understanding the interaction with electric field, but also that membrane depolarization far below the firing threshold can influence the activity of neuronal networks. Second, among the reported effects in humans, let us mention the modulation of pain threshold (Ghione et al, 2005), effects on resting tremor (Legros and Beuter, 2005), modulations in functional brain activity as measured by BOLD (Legros et al, 2011), interference with learning in a short-term memory test (Corbacio et al, 2011). The most established interaction mechanism of MF exposure consists in induced currents, resulting from Faraday's law of induction, stating that a time-varying MF induces a time-varying electric field.…”
Section: Introductionmentioning
confidence: 99%